VONIS HAKIM YANG MEMISKINKAN KORUPTOR - Fanny Tanuwijaya (Faculty of Law, Universitas Diponegoro, 2014)
Default Paragraph Font;hps;short_text;Verdict impoverish corruptors by Judge not only considered to uphold the juridical norms, but also to implements the code of professional conduct as a judge. Impoverishment corruptors will have positive impact on the image of Indonesia as a state of law and prevention of corruption. For corruption, this can cause a deterrent effect, which then can prevent anyone who wants to involved in corruption. However, the verdict of impoverishing for corruptors is determined by the judges consistency in implementing the code of conduct of his profession